The influence of gut microbiota on the gut-brain-kidney axis and its implications for chronic kidney disease - Zhu, Jue; Fu, Yutong; Olovo, Chinasa Valerie; Xu, Jianguo; Wu, Qian; Wei, Wei; Jiang, Ke; Zheng, Xueming (Frontiers in Microbiology, 2025)
The gut-brain-kidney axis represents a dynamic interplay among the gut microbiota, renal function, and neurological processes, emerging as a critical factor in chronic kidney disease (CKD) pathophysiology. This paper reviews recent data on the mechanisms and pathways that integrate gut-brain-kidney signaling and communication, advances in our understanding of this axis, and potential diagnostic and prognostic biomarkers and interventions for CKD. Literature search was conducted on PubMed, Scopus, Web of Science, and Embase using a combination of the keywords gut microbiota, gut microbiome, gut-brain axis, gut-kidney axis, gut-brain-kidney axis, chronic kidney disease, dysbiosis, therapy, metabolites, and neuroinflammation.” Relevant studies were selected and synthesized in this narrative review. Gut dysbiosis, characterized by microbial composition and function alterations, contributes to systemic inflammation and metabolic imbalances, exacerbating CKD progression. Uremic toxins such as indoxyl sulfate and p-cresyl sulfate, derived from microbial metabolism, impair kidney function and disrupt neurocognitive health via oxidative stress and neuroinflammation, highlighting the interconnectedness of these systems. Recent advances in high-throughput sequencing and metabolomics have elucidated mechanisms linking gut microbiota and associated metabolites to kidney and brain health, revealing the role of microbial diversity and metabolite profiles in disease outcomes. Studies demonstrate that probiotics, prebiotics, and dietary interventions targeting the gut microbiota can modulate systemic inflammation and reduce uremic toxin levels, offering therapeutic potential. Understanding the bidirectional signaling within the gut-brain-kidney axis opens avenues for novel biomarkers and interventions in CKD management.